Efficient electricity generating portfolios for Europe: Maximising energy security and climate change mitigation - Shimon Awerbuch; Spencer Yang (EIB Papers, 2007)
This paper applies portfolio-theory optimisation concepts from the field of finance to produce an expository evaluation of the 2020 projected EU-BAU (business-as-usual) electricity generating mix. We locate optimal generating portfolios that reduce cost and market risk as well as CO2 emissions relative to the BAU mix. Optimal generating portfolios generally include greater shares of wind, nuclear, and other nonfossil technologies that often cost more on a standalone engineering basis, but overall costs and risks are reduced because of the portfolio diversification effect. They also enhance energy security. The benefit streams created by these optimal mixes warrant current investments of about exteuro250 - exteuro500 billion. The analysis further suggests that the optimal 2020 generating mix is constrained by shortages of wind, especially offshore, and possibly nuclear power, so that even small incremental additions of these two technologies will provide sizeable cost and risk reductions.
Keywords: 330